Editorial for "Radiomics based on multimodal MRI for the differential diagnosis of benign and malignant breast lesions" - Nogueira, Luisa (2021)
Breast magnetic resonance imaging (MRI) is widely used to detect and characterize lesions, presenting good sensi- tivity but moderate specificity. To improve accuracy, new MRI sequences are continuously being sought. Diffusion- weighted imaging (DWI) probes the lesions’ cellularity, improving specificity. However, the distributions of the apparent diffusion coefficients (ADCs) for different lesion types show an overlap. Extensions to the monoexponential DWI model have thus been proposed such as diffusion- kurtosis imaging (DKI).